Systematic Review of Angiotensin-Converting Enzyme Inhibitors and Calcium Channel Blockers in Ischemic Stroke Prevention: Evaluating the Comparative Effectiveness of ACE Inhibitors and Calcium Channel Blockers for Secondary Stroke Prevention - Hasanah, Miftahul; Avini Mawarni Soedarsono (Acta Neurologica Indonesia, 2025)
Introduction : Ischemic stroke is a leading cause of disability and death worldwide, with hypertension being one of the most significant modifiable risk factors. Among antihypertensive agents, ACE Inhibitors (ACEIs) and Calcium Channel Blockers (CCBs) are commonly used. However, their relative efficacy in preventing ischemic stroke remains a subject of clinical interest. Methods : A systematic search was conducted using PubMed, Cochrane Library, and ScienceDirect for articles published between 2010 and 2025. Eligible studies included research article that evaluated the effect of ACE inhibitors or Calcium Channel Blockers on the prevention of ischemic stroke in adults with hypertension. Reviewers independently screened titles, abstracts, and full texts, and extracted data. Study quality was assessed using the Cochrane Risk of Bias tool. Results : From 8,991 screened articles, 17 studies met the inclusion criteria. Both ACE inhibitors and Calcium Channel Blockers showed effectiveness in reducing ischemic stroke risk. Some studies showed a slightly better effect with Calcium Channel Blockers like amlodipine, while others reported similar results between ACE inhibitors and Calcium Channel Blockers. Differences in study designs and patient groups made direct comparison difficult. Discussion : Both ACE Inhibitors and Calcium Channel Blockers are effective in reducing the risk of ischemic stroke in hypertensive patients, although the relative benefit between the two remains complex. Calcium Channel Blockers may offer a slight advantage in certain populations, but ACE Inhibitors continue to be a cornerstone of stroke prevention strategies, particularly in patients with additional cardiovascular risk factors. Keywords : ACEi, CCBs, Stroke, Systematic Review